Analisis Teras Berita pada Surat Kabar Harian Tribun Pekanbaru - Helsy Arides Hanyuli; Muhammad Mukhlis (Sajak: Jurnal Penelitian dan Pengabdian Sastra, Bahasa, dan Pendidikan, 2023)
The research method used was that this research was carried out in Pekanbaru in 2020. Furthermore, this research method used a qualitative descriptive method with the aim of describing the writing style of news headlines in the headlines of the Pekanbaru Tribune newspaper which were found in the research as is. The term "descriptive" is one of the characteristics of qualitative research. Therefore, this research is also called qualitative research, whose characteristics appear in the description of the research data, data collection, data analysis, and presentation of the results of data analysis. The data collection technique in this study is the data collection technique is the main step in conducting this research, because the main purpose of this research is to obtain data. The techniques used to obtain data in this study are documentation techniques. agendas and so on. The data that the author obtained were 30 data from the Tribun Pekanbaru Newspaper. Hermeneutic techniques are techniques of reading, noting, and summarizing. The author does this technique with the aim of getting the data that is examined. Here, the author first reads the newspapers contained in the Pekanbaru Tribune newspaper, then records the words included in the types of headlines in the editorial. Data taken as many as 30 data from the Pekanbaru Tribune Newspaper.